Collecting Self-Reported Data on Dating Abuse Perpetration From a Sample of Primarily Black and Hispanic, Urban-Residing, Young Adults: A Comparison of Timeline Followback Interview and Interactive Voice Response Methods. Issue 1 (January 2020) - Rothman, Emily F.; Heeren, Timothy; Winter, Michael; Dorfman, David; Baughman, Allyson; Stuart, Gregory
Dating abuse is a prevalent and consequential public health problem. However, relatively few studies have compared methods of collecting self-report data on dating abuse perpetration. This study compares two data collection methods—(a) the Timeline Followback (TLFB) retrospective reporting method, which makes use of a written calendar to prompt respondents' recall, and (b) an interactive voice response (IVR) system, which is a prospective telephone-based database system that necessitates respondents calling in and entering data using their telephone keypads. We collected 84 days of data on young adult dating abuse perpetration using IVR from a total of 60 respondents. Of these respondents, 41 (68%) completed a TLFB retrospective report pertaining to the same 84-day period after that time period had ended. A greater number of more severe dating abuse perpetration events were reported via the IVR system. Participants who reported any dating abuse perpetration were more likely to report more frequent abuse perpetration via the IVR than the TLFB (i.e., may have minimized the number of times they perpetrated dating abuse on the TLFB). The TLFB method did not result in a tapering off of reported events past the first week as it has in prior studies, but the IVR method did result in a tapering off of reported events after approximately the sixth week. We conclude that using an IVR system for self-reports of dating abuse perpetration may not have substantial advantages over using a TLFB method, but researchers' choice of mode may vary by research question, resources, sample, and setting.